Characterisation of α-glucosidase inhibitors from Clinacanthus nutans (Burm.f.) Lindau leaves extract using metabolomics approach and molecular docking simulation - Suganya Murugesu (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
The use of medicinal plants to combat various diseases has grown intensively due to the side effects from commercial synthetic drugs. Clinacanthus nutans (Burm.f.) Lindau is a traditional medicinal plant native to Malaysia, yet to be explored for its antidiabetic effect. Therefore, this study aimed to investigate the antidiabetic potential of the plant using metabolomics approach and molecular docking simulation. The 80% methanolic crude extract of this plant leaves was partitioned using different polarity solvents viz., n-hexane, n-hexane: ethyl acetate (1:1, v/v), ethyl acetate, ethyl acetate: methanol (1:1, v/v) and methanol. All fractions were screened for antioxidant and antidiabetic activity via bioassays techniques. The α-glucosidase inhibitors of the plant were identified using gas and liquid chromatography fitted with mass spectrometry (GCMS and LCMS, respectively) based metabolomics. All the inhibitors identified were then docked to α-glucosidase enzyme crystal structure to predict its ligand-protein interaction. The study also developed a validated regression model using Fourier transform infrared (FTIR) spectroscopy. Lastly, the most active fraction was investigated for its toxicity level using zebrafish (Danio rerio) embryos. Despite a moderate antioxidant capacity, n-hexane fraction exhibited a good α-glucosidase and dipeptidyl peptidase-IV inhibiting activities. The n-hexane fraction also improved glucose uptake in a dose-dependent manner. Chemical profiling utilising GCMS based metabolomics derived 11 bioactive compounds namely; palmitic acid, phytol, hexadecanoic acid (methyl ester), 1-monopalmitin, stigmast-5-ene, pentadecanoic acid, heptadecanoic acid, 1-linolenoylglycerol, glycerol monostearate, α-tocospiro B and stigmasterol corresponding to the distinct biological activity. Meanwhile, LCMS revealed 4 compounds tentatively identified as; 4,6,8-megastigmatrien-3-one; N-isobutyl-2-nonen-6,8-diynamide; 1',2'-bis(acetyloxy)-3',4'-didehydro-2'-hydro-β, ψ-carotene and 22-acetate-3-hydroxy-21-(6-methyl-2,4-octadienoate)-olean-12-en-28-oic acid. The docking results predicted the interaction of all the identified compounds to be in non-competitive mode with majorly involving hydrophobic interactions with the protein residues. Some of the residues involved include LYS156, THR310, PRO312, LEU313, GLU411 and ASN415, etc with hydrogen bond while TRP15, VAL232, HIE280, ALA292, PHE314, ARG315, etc in hydrophobic contact. The partial least square model generated using FTIR analysis was validated using external sample and could potentially predict the α-glucosidase inhibitory activity of C. nutans leaves extracts thus can be applied for quality control purposes. The toxicity assessment showed the morphological defects caused by n-hexane fraction such as hyperactivity, delayed hatching, crooked backbone, reduced pigmentation, awkward position and oedema at 125 µg/mL. The LC50 value was calculated to be 75.49 µg/mL. However, the plant extract can be developed as an antidiabetic agent after the removal of the toxicants. Conclusively, the metabolomics approach in this study has revealed the antidiabetic potential of C. nutans leaves through identification of the active α-glucosidase inhibitors from this plant.